Survey to assess knowledge about polycystic ovarian syndrome in females of reproductive age group: a hospital-based study - Rehal, Taranpreet; Cheema, Harwinder K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Polycystic Ovarian Syndrome (PCOS) is the most common endocrine disorder affecting women of reproductive age. Many women remain undiagnosed due to lack of awareness about its signs, symptoms, and complications and associated risk factors. Educating women about PCOS is key for early diagnosis and effective management. This study aims to asses knowledge about PCOS in females of reproductive age group. Methods: A cross-sectional observational study was conducted from June to August 2023 at the gynaecology OPD of Punjab Institute of Medical Sciences, Jalandhar. A total of 150 women aged 18–45 years participated by filling a structured and validated questionnaire designed in English and Punjabi. Data were analysed using MS excel. Results: The majority of respondents (54.7%) were aged 21–30 years and from urban areas (64.7%). Most were students (50%) with education up to 10+2 (49.3%). Awareness of PCOS symptoms varied, with obesity (66%), hair loss (63.3%), and acne/oily skin (59.3%) being the most recognized. Only 38% identified junk food as a risk factor, while 52.7% believed obesity leads to PCOS. Complications like ovarian cancer (29.3%) and diabetes mellitus (24.7%) were less recognized. Awareness about lifestyle modifications such as healthy diet (83.3%) and regular exercise (79.3%) was high. Health workers (76.7%) were the primary source of information. Conclusions: There is a significant gap in knowledge about PCOS among reproductive-age females. Increased awareness through education, seminars, and counselling is essential for early detection and prevention. Health seeking behaviour should be encouraged.